O lúdico na aquisição do letramento: os jogos educativos - PIRES, Iracy Silva (2019)
The Ludic in the acquisition of literacy, educational games, literacy and literacy have been the key point of many discussions around the world in Brazil can highlight that in a way still and a new theme is considerably of great importance for our children. Literacy in a way is the acquisition that people through reading and writing skills acquire in a specific context and with those skills relate to social needs, values and practices. This study aims to analyze through a case study how literacy and literacy are given in the 3rd grade class of the "King of Kings" school so that we can understand the importance of literacy and literacy by middle of the appropriating playful of educational games. I have come through this work to investigate how the play can contribute to the acquisition of literacy and literacy. The case study will be carried out through observation and thus shows within the analyzes how literacy and literacy are being performed in the 3rd grade class. For this, it was necessary to appropriate games and differentiated methodology. In order to carry out this work it was necessary to read based on theorists who make several approaches such as KISHIMOTO (1990), PIAGET (1973) SOARES (2010) VIGOTSKY (1989). Therefore we can emphasize that literacy and literacy do not occur overnight everything happens through a process that must be worked out clearly and well planned.